Data Security and Cybersecurity in Saudi Arabia (Eurasian Journal of Engineering and Technology, 2023)
This research paper aimed to assess the current state of data security and cybersecurity in Saudi Arabia, identify key challenges and obstacles, and propose recommendations for improvement. To achieve this goal, a systematic review of academic studies and practical case studies conducted between 2020 and 2023 was utilized, along with an analysis of survey data, literature reviews, and expert insights, to gather comprehensive information on the subject matter. The findings of the study revealed significant areas of concern, such as the lack of cybersecurity awareness and training in Saudi Arabian organizations, accompanied by a shortage of resources and expertise in this field. The increasing complexity and diversity of cyber threats further compound the challenges. For instance, the study found that the lack of a comprehensive cybersecurity framework and national strategy hinders the country's ability to respond effectively to cyber threats.  However, the study also identified opportunities presented by emerging technologies, such as artificial intelligence and blockchain, for enhancing cybersecurity practices. These technologies can potentially strengthen security measures and improve threat detection capabilities. Nevertheless, their adoption requires careful consideration of the associated risks.Considering these findings, the study proposed several recommendations to address these challenges. Firstly, organizations in Saudi Arabia should prioritize cybersecurity awareness and training programs to enhance their preparedness. Allocating sufficient resources and expertise is essential to developing comprehensive cybersecurity frameworks and policies. Furthermore, the study emphasized the importance of a national cybersecurity strategy to guide efforts to improve cybersecurity practices across the country. Additionally, organizations should explore the potential of emerging technologies while evaluating and mitigating the associated risks. Regular cybersecurity risk assessments and audits are crucial to identifying vulnerabilities and enhancing cybersecurity readiness.Implementing these recommendations can significantly enhance data security and cybersecurity practices in Saudi Arabia. They provide a roadmap for organizations to effectively respond to the evolving threat landscape and mitigate cybersecurity risks in an increasingly digital environment. The study's findings and recommendations can help policymakers and organizations in Saudi Arabia make informed decisions about cybersecurity investments and strategies, ultimately improving the country's cybersecurity posture.